1999
DOI: 10.1890/0012-9658(1999)080[1180:mieceo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizae Indirectly Enhance Competitive Effects of an Invasive Forb on a Native Bunchgrass

Abstract: Mycorrhizae are important mediators of plant competition, but little is known about the role of mycorrhizae in the intense competitive effects that exotic plants can have on native species. In the greenhouse, we tested the effect of arbuscular mycorrhizal (AM) fungi on interspecific competition between Centaurea maculosa and Festuca idahoensis, on intraspecific competition between individuals of both species, and the growth of C. maculosa with either inorganic or organic phosphorus. Mycorrhizae had no direct e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
124
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 328 publications
(137 citation statements)
references
References 50 publications
9
124
2
2
Order By: Relevance
“…In an extensive assessment of responses by 36 species of warm-and cool-season prairie grasses and 59 prairie forbs to arbuscular mycorrhizal (AM) fungal colonization, Wilson and Hartnett (1998) showed that biomass was enhanced by mycorrhizae in C 4 grasses and forbs, but not C 3 grasses or annuals. However, several other studies suggest that mycorrhizae may also benefit competitive subdominants (Walter et al 1996, Marler et al 1999.…”
Section: Establishment Of C 4 Grass Dominancementioning
confidence: 99%
“…In an extensive assessment of responses by 36 species of warm-and cool-season prairie grasses and 59 prairie forbs to arbuscular mycorrhizal (AM) fungal colonization, Wilson and Hartnett (1998) showed that biomass was enhanced by mycorrhizae in C 4 grasses and forbs, but not C 3 grasses or annuals. However, several other studies suggest that mycorrhizae may also benefit competitive subdominants (Walter et al 1996, Marler et al 1999.…”
Section: Establishment Of C 4 Grass Dominancementioning
confidence: 99%
“…As parasitic plants are common in natural communities (Pennings & Callaway, 2002), invasive plants may interact simultaneously with native plants, soil microbes, and native parasitic plants (Li, Jin, Hagedorn, & Li, 2014). Empirical studies have shown that soil microbial communities can mediate competitive interactions between invasive plants and native plants (e.g., Allen, Meyerson, Flick, & Cronin, 2018;Lankau, 2010;Marler, Zabinski, & Callaway, 1999;Shivega & Aldrich-Wolfe, 2017). For example, rhizospheric soil biota of the invader Phragmites australis increased biomass of a native plant Spartina alterniflora when the two plant species were grown in competition with each other (Allen et al, 2018).…”
mentioning
confidence: 99%
“…In pairwise competition experiments that compared performance of two native prairie plants (Oligoneuron rigidum and Andropogon gerardii) against one invader (Carduus acanthoides), the native plants fared better against the invader in the presence of a native microbial community (Shivega & Aldrich-Wolfe, 2017). AM fungi increased the negative effects of the invader Centaurea maculosa on a native bunchgrass Festuca idahoensis (Marler et al, 1999). Studies have also shown that native parasitic plants can affect competition between invasive host plants and co-occurring native plants.…”
mentioning
confidence: 99%
“…It was also found that AMF promoted Microstegium vimineum biomass, increased P uptake, and altered plant morphology, increasing the number of stolons and aerial roots (Lee et al 2014). Centaurea stoebe exhibited a positive growth response to AMF, either growing alone (Harner et al 2010) or with some neighboring plants from which it can exploit resources via mycelia (Marler et al 1999; Zabinski et al 2002; Callaway et al 2004; Carey et al 2004). Bray et al (2003) demonstrated that the relative growth rates and leaf area ratio of Ardisia crenata were higher for AMF-inoculated seedlings.…”
Section: Introductionmentioning
confidence: 99%